Capacitive Sodium‐Ion Storage Based on Double‐Layered Mesoporous Graphene with High Capacity and Charging/Discharging Rate. Issue 18 (18th June 2019) - Zhu, Xiao; Jiang, Qinyuan; Wang, Tianshuai; Zhang, Qianfan; Jia, Xilai; Zhang, Rufan
Abstract: Sodium‐ion batteries (SIBs) are regarded as an ideal alternative to lithium‐ion batteries, but the larger radius of Na + compared with Li + results in lower energy density, shorter cycle life, and sluggish kinetics of SIBs. Therefore, it is of significant importance to explore appropriate Na + storage materials with high capacity and fast Na + transport kinetics. Herein, doublelayered mesoporous graphene nanosheets codoped with oxygen and nitrogen (O, N‐MGNSs) were developed as a new cathode material with high Na + storage capacity and fast ion‐transport kinetics for SIBs. The codoping of MGNSs with oxygen and nitrogen by in situ chemical vapor deposition endowed them with a hierarchical porous network, robust structures, good conductivity, and abundant functional groups. The O, N‐MGNSs could host Na + in two ways: surface adsorption and surface redox reaction, and this endowed them with high Na + storage capacity and fast charging/discharging rates in SIBs. Electrochemical results revealed that the O, N‐MGNSs delivered a reversible capacity of 156 mAh g −1 at a current density of 0.5 A g −1 (corresponding to a rate of 3 C) between 1.5 and 4.2 V and exhibited a high cycling stability (95 % capacity retention at 1 A g −1 for more than 1000 cycles). Abstract : High sodium intake : Double‐layered mesoporous graphene nanosheets codoped with oxygen and nitrogen by in situ chemical vapor deposition are prepared for use as sodium‐ion battery cathode materials with high sodium storage capacity and fast charging/discharging through surface adsorption and surface redox reactions.